Peran Komunitas Gerakan Pemuda Masjid Medan Timur Dalam Penguatan Aqidah Masyarakat Islam di Desa Rante Besi, Kecamatan Gunung Sitember, Kabupaten Dairi - Hamid Muzakki (UIN Sumatera Utara, 2021)
This article wants to explore the role played by a youth movement community at the East Medan mosque in strengthening the aqidah of the Islamic community in Rante Besi village, Gunung Sitember sub-district, Dairi district. The area, which is quite far from the city of Sidikalang, is a remote area that takes quite a long time to travel in damaged and steep road conditions. Rante Besi Village is one of the villages located in Gunung Sitember District, Dairi Regency, a village that has a variety of tribes, languages and religions that it adheres to has a Muslim population that is considered a minority, this is one of the reasons for the lack of practice of the Islamic creed and the many worship practices that are not in accordance with the Shari'a and deviations from the Islamic Aqeedah. There is one hamlet in Rente Besi Village which is expected to be a strong potential and hope for the development of Islamic Aqeedah in the midst of society because of the majority of the hamlet population. This study discusses how the role of the youth movement community of the East Medan mosque in strengthening the Aqidah of the Islamic community as a youth movement that has awareness of the development of Islam and social care which is then expected to be a magnet for generating enthusiasm for Islamic youth to use their youth for things that are good for them. positive and useful for many people.